Il mito delle Danaidi su un cratere napoletano - Benincasa, Alfonsina (O T I V M, 2017)
The myth of Danaides is well-known from the literary sources: they are punished and in the second moment they are purified by a ritual that consisted in pouring water in a pithos. In some ancient texts the Danaides are related to ἀμύητοι that are punished in the Underworld to pour water in a pithos without bottom. The iconography of Danaides is documented frequently in apulian figured pottery and it is connected with the iconography of others damned in representations of afterlife. In this context I would focus the attention on a volute krater by the Arpi Painter, of the last quarter of IV century B.C. It belongs to Neapolitan private collection. The subject in this case has treated in original way, first of all for the number of girls, especially because the penance/punishment takes place probably inside a building similar to the house of Hades. The presence of a afterlife demon is characteristic too: he is Eurynomos, whose presence refers to Nekyia of Polygnotos in the Cnidian Lesche in Delphi, whose Pausanias speaks in his Description of Greece. Aformentioned elements lead one to think that there is a well-read reelaborated version of myth, represented inside the house of Hades. This version isn’t unknown to redeeming messagges connected by eleusinian mysteries like in the Polygnotean Nekyia. The centrality of Danaides implies moreover the value of purification in the passagge’s ritual of girls through the wedding. In the first time the purification is called to mind through the refusal of marriage, in the second time, after the transformation of the girls into friendly water nymphs, through their second wedding.